Secondee management: Theoretical issues and current practice in Vietnam - Pham Thi Thanh Tuyen; Hoang Thi Dao; Hoang Truong Giang (Petrovietnam Journal, 2015)
Secondee is often defined as a member of staff of a corporation who is transferred to a subsidiary to act on behalf of the owners for a fixed period of time. During the secondment process, the secondee plays an important role in realising the owner’s strategic objectives. In Vietnam, the concept of secondee is still inconsistent and the provisions on secondee management are not fully detailed in laws or in organisations’ internal regulations. Furthermore, the remuneration of secondees is not yet based on responsibility and performance; therefore, many problems exist in secondee management. The aim of this paper is to clarify the concept of secondee and to specify the relationship of three parties: the secondee, the secondee’s organisation, and the host organisation. By analysing current practices on secondee management in the world, the authors suggest some lessons for secondee management in Vietnam.